Poverty Reduction and Growth Trust-2020-21 Borrowing Agreements with The Government of Canada as Represented by The Minister of Finance, and The People's Bank of China. (Policy Papers; Policy Paper ;, 2021)
This paper presents two new borrowing agreements for the Poverty Reduction and Growth Trust (PRGT). These two agreements with the IMF, acting as Trustee for the PRGT, and the Government of Canada and the People's Bank of China respectively have been finalized as part of the resource mobilization effort in response to the unprecedented demand for concessional financing driven by the COVID-19 pandemic and ensuing economic shocks. The fast-track loan mobilization round launched in April 2020 allowed the Fund to increase access limits and scale up emergency financing to low-income countries (LICs). To date, eleven new agreements and the augmentation of five existing agreements have been finalized with sixteen lenders (for previous updates see the October 2020 paper and the March 2021 paper. Together, these agreements and augmentations provide a total of SDR 16.9 billion in new PRGT loan resources for LICs, of which SDR 15.1 billion is immediately available.